Resolução de problemas: a conexão entre matemática e física por meio da função afim e quadrática - Barreto, Nathanael de Sousa (2019)
This study shows the various benefits proposed by the methodology of problem solving through affine and quadratic functions. The research also uses the connection between mathematics and physics as an important factor in understanding some movements, and has this relationship as a motivation for students to continue studying mathematics. It was carried out in a public school in the city of Anajatuba- MA with students from the 1st and 3rd grades of high school. Through problem solving, the research showed the benefits of the methodology to education when it was possible to achieve a variety of objectives such as: connection between mathematics and physics, better interpretation of texts, connecting mathematics to the real world, motivating the study of mathematics, associating content in contextualized problem situations